Differential regulation of auxin and cytokinin during the secondary vascular tissue regeneration in Populus trees. Issue 1 (2nd August 2019) - Chen, Jia‐Jia; Wang, Ling‐Yan; Immanen, Juha; Nieminen, Kaisa; Spicer, Rachel; Helariutta, Ykä; Zhang, Jing; He, Xin‐Qiang
Summary: Tissue regeneration upon wounding in plants highlights the developmental plasticity of plants. Previous studies have described the morphological and molecular changes of secondary vascular tissue (SVT) regeneration after large‐scale bark girdling in trees. However, how phytohormones regulate SVT regeneration is still unknown. Here, we established a novel in vitro SVT regeneration system in the hybrid aspen ( Populus tremula × Populus tremuloides ) clone T89 to bypass the limitation of using field‐grown trees. The effects of phytohormones on SVT regeneration were investigated by applying exogenous hormones and utilizing various transgenic trees. Vascular tissue‐specific markers and hormonal response factors were also examined during SVT regeneration. Using this in vitro regeneration system, we demonstrated that auxin and cytokinin differentially regulate phloem and cambium regeneration. Whereas auxin is sufficient to induce regeneration of phloem prior to continuous cambium restoration, cytokinin only promotes the formation of new phloem, not cambium. The positive role of cytokinin on phloem regeneration was further confirmed in cytokinin overexpression trees. Analysis of a DR5 reporter transgenic line further suggested that cytokinin blocks the re‐establishment of auxin gradients, which is required for the cambium formation. Investigation on the auxin and cytokinin signalling genes indicated these two hormones interact to regulate SVT regeneration. Taken together, the in vitro SVT regeneration system allows us to make use of various molecular and genetic tools to investigate SVT regeneration. Our results confirmed that complementary auxin and cytokinin domains are required for phloem and cambium reconstruction.